Characterization of pavement texture by means of height difference correlation and relation to wet skid resistance - Stefan Torbruegge; Burkhard Wies (Journal of Traffic and Transportation Engineering (English ed. Online), 2015)
Driving safety is of utmost importance in the automobile industry and is acknowledged by the introduction of the tire wet grip index as part of the EU tire label. The rubber pavement interaction is determined by the viscoelastic properties of the rubber as well as by the pavement texture. Nowadays available optical surface profiling instruments allow for a detailed measurement of surface roughness covering several length scales. This enables the validation of a mathematical statistical description of pavement texture within the framework of self-affine surfaces and hence provides a holistic characterization of surface roughness covering several length scales within a few characteristic parameters. We deduce within this article the correlation between classical surface roughness parameters and the parameter set of self-affine surfaces. These parameters allow for a detailed understanding of the relationship between pavement texture and its wet skid resistance. We present wet skid resistance measurements with the British pendulum and a linear friction tester device on different pavement textures. We demonstrate that the so-called estimated texture depth does not correlate to the surface skid resistance measured with the British pendulum. Finally, we deduce a dependency of wet skid resistance on pavement texture which is supported by current models for hysteresis friction.